Examining the divergent effects of perceived inclusion of ethnic minorities on majority and minority groups’ inter-ethnic responses - Andriessen, Iris; Gündemir, Seval; Kappelhof, Joost W. S.; Homan, Astrid C. (Frontiers in Psychology, 2023)
This study examines the paradoxical effects of a perceived inclusive environment for ethnic minorities. We argue that while perceptions of an inclusive environment may be associated with more positive intergroup attitudes and affect among minority groups, they may instill a sense of threat among the majority group, resulting in negative intergroup sentiments and attitudes towards minorities. We analyzed data from two waves of a nationally representative survey conducted in the Netherlands (ntotal = 11,897) comprising minority and majority groups. We find support for the proposed paradoxical relationship between the perceived inclusionary climate towards minorities and the attitudes of the majority and minority groups. The results indicate that when perceiving the national climate to be more inclusive towards minorities, the majority group tends to report higher levels of ethnocentrism, avoid direct inter-ethnic contact, and oppose ethnic diversity in general. Among minority groups, a perceived inclusive climate is linked to lower levels of ethnocentrism and a higher willingness to engage in inter-ethnic interactions with the majority group. The results unexpectedly also show that the perception of an inclusionary climate is positively related to opposition to increased ethnic diversity among minority groups. We discuss theoretical and societal implications, while also considering the contextual relevance and limitations of our approach.